2017
DOI: 10.4314/ejst.v10i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of time to microvascular complications among diabetes mellitus patients using parametric and non-parametric approaches: a case study of Ayder referral hospital, Ethiopia

Abstract: Socio-demographic and clinical factors have been known to affect the time to microvascular complications and survival probabilities of diabetes mellitus patients. The objective of this study was to identify risk factors and estimate average survival times for the time to the development of microvascular complications of diabetic patients under follow up at Ayder referral hospital from February 2011 to January 2014. A retrospective follow up study was conducted on diabetic patients during this treatment period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…The risk of developing DR among Type 2 DM patients was higher than among Type 1 DM patients in this study. The result is similar to the study conducted at Ayder referral hospital in Ethiopia and noted that type 2 DM patients had a shorter time to developing microvascular DM complications than Type 1 DM patients [ 39 ]. This may be due to the older age of most of the Type 2 patients and their inability to support themselves to receive appropriate eye screening services [ 43 ].…”
Section: Main Textsupporting
confidence: 87%
See 1 more Smart Citation
“…The risk of developing DR among Type 2 DM patients was higher than among Type 1 DM patients in this study. The result is similar to the study conducted at Ayder referral hospital in Ethiopia and noted that type 2 DM patients had a shorter time to developing microvascular DM complications than Type 1 DM patients [ 39 ]. This may be due to the older age of most of the Type 2 patients and their inability to support themselves to receive appropriate eye screening services [ 43 ].…”
Section: Main Textsupporting
confidence: 87%
“…This might be due to the fact that neuroretinal function is more abnormal in adult males than in adult females [ 38 ]. However, a study conducted in Ethiopia [ 39 ] showed that males had a lower risk of developing microvascular complications of DM than females.…”
Section: Main Textmentioning
confidence: 99%
“…Hence, the average disease-free survival time for T2DM patients was 0.40 times that of T1DM patients. This finding is analogous to the studies conducted at Ayder referral hospital 41 and Tikur Anbessa Hospital 32 in Ethiopia, which found that T2DM patients had higher risk of developing DR and other microvascular complications than T1DM patients. This could be due to the fact that most of the T2DM patients are older compared to T1DM patients.…”
Section: Discussionsupporting
confidence: 87%
“…This could be due to a combination effect of insulin resistance and predominately a loss of beta cells in advanced age, which results in poor glycemic control and greater microvascular damage ( 31 ). Higher FBS levels showed a significant association with the development of diabetic microvascular complications, as has been observed in previous studies conducted in Ethiopia and Saudi Arabia ( 22 , 26 ). This might be associated with the high blood sugar level for longer periods effect of cell damage mainly occurs in capillary endothelial cells of the retina, mesangial cells of the renal glomerulus, neurons, and Schwann cells of peripheral nerves, causing diabetic microvascular complications ( 32 ).…”
Section: Discussionsupporting
confidence: 84%
“…Microvascular complications are present in half of patients with T2DM ( 8 ). In previous studies conducted, the prevalence of microvascular complications was 18.0%-57.5% in Asia ( 13 16 ), 34.3%-48.4% in the Middle East ( 17 19 ), 47.8% in Nigeria ( 20 ), and 19.5%-42.6% in Ethiopia ( 21 – 26 ). Duration of diabetes, hypertension, triglycerides, age, dyslipidemia, poor glycemic control, sex, systolic blood pressure, and positive proteinuria were commonly associated factors with the development of diabetic microvascular complications in previous studies ( 13 , 14 , 16 , 17 , 21 , 22 , 24 27 ).…”
Section: Introductionmentioning
confidence: 91%